PEMBIASAAN SHOLAT DHUHA BERJAMA’AH TERHADAP PENDIDIKAN KARAKTER SISWA DI SMP MUHAMMADIYAH 4 SAMBI - Saryadi Saryadi; Septy Nur Amalia Putri; Hastin Puspitasari; Endang Setyaningsih (Buletin Literasi Budaya Sekolah, 2020)
Strengthening character education (PPK) is one of the created by the government which aims to create the next generation of the nation who is academically intelligent and also physically and mentally intelligent. Strengthening Character Education that is commonly done is by doing habituation. One of the ways of character education in the form of habituation that has been implemented by SMP Muhammadiyah 4 Sambi is by habituating the implementation of dhuha prayers in congregation. This research was conducted to determine the benefits of practicing dhuha prayer at SMP Muhammadiyah 4 Sambi, which was carried out during the Introduction to Preschool Environment 1 (PLP1) program between 2 weeks, in February 2020 using descriptive methods with qualitative data. The results of this study indicate that the habituation of dhuha prayer in congregation as a strengthening of character education carried out by students at SMP Muhammadiyah 4 Sambi is positive towards student character such as the character likes to establish friendship between students, the character of mutual respect and respect, the character is accustomed to remembering and getting closer. self to the creator, the character of the loss of excessive individualism, and the character of discipline to come on time to school, do good activities repeatedly, and discipline to carry out religious orders. From this it can be said that indeed the habituation of dhuha prayer activities in congregation is beneficial to the character of students.